2006
DOI: 10.1590/s0066-782x2006000600006
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco cardiovasculares em adolescentes: indicadores biológicos e comportamentais

Abstract: The results reinforce the need for interventions targeted at the adoption of a healthy lifestyle, including the regular practice of physical exercise, appropriate dietary patterns, and abstention from smoking as of an early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
53

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 57 publications
4
25
1
53
Order By: Relevance
“…Foi considerado como etilista e tabagista, respectivamente, o adolescente que referiu consumir, pelo menos, uma dose de bebida alcoólica e fumar um ou mais cigarros durante uma semana típica/habitual 9,17 . O índice de massa corporal (IMC = massa corporal [kg] / estatura [m²]) foi obtido com base nas medidas autorreferidas pelos adolescentes de massa corporal (kg) e estatura (cm) 18 .…”
Section: Métodounclassified
See 1 more Smart Citation
“…Foi considerado como etilista e tabagista, respectivamente, o adolescente que referiu consumir, pelo menos, uma dose de bebida alcoólica e fumar um ou mais cigarros durante uma semana típica/habitual 9,17 . O índice de massa corporal (IMC = massa corporal [kg] / estatura [m²]) foi obtido com base nas medidas autorreferidas pelos adolescentes de massa corporal (kg) e estatura (cm) 18 .…”
Section: Métodounclassified
“…A presença de fatores de risco nessa fase da vida, principalmente de forma simultânea (co-ocorrência), tem se configurado como um forte preditor de DCV na idade adulta 4,5 . Resultados de diversas pesquisas com adolescentes de diferentes países [6][7][8] , inclusive no Brasil [9][10][11] , demonstraram prevalências elevadas de fatores de risco cardiovascular. Contudo, dados sobre a prevalência de simultaneidade de fatores de risco e sua distribuição em função de indicadores sociodemográficos ainda são escassos, principalmente em adolescentes brasileiros, e mais ainda da região Nordeste.…”
Section: Introductionunclassified
“…Guedes et al 12 have also not found an association between physical activity and total and HDL-c. However, LeBlanc & Janssen 24 found that small amounts of moderate to vigorous physical activity reduced the risk of low HDL-c levels.…”
Section: Discussionmentioning
confidence: 88%
“…However, LeBlanc & Janssen 24 found that small amounts of moderate to vigorous physical activity reduced the risk of low HDL-c levels. Moreover, studies suggest that a diet high in fats, cholesterol, and sodium, and poor in fibers can have a negative impact on the lipid profile of adolescents 12,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation